Analisis Strategi Optimasi Mutu Laporan Keuangan Pemerintah Kota Bogor - Mochamad Ramdani; Dwi Rachmina; Anna Fariyanti (Jurnal Manajemen Pembangunan Daerah, 2024)
ABSTRACT The local government, as a budget user institution, is responsible for realizing transparency and accountability in financial management by submitting accountability reports in the form of financial statements that will be audited by the Supreme Audit Agency (BPK). The audit results report (LHP) of the Bogor City Government's financial statements from 2006 to 2015 received a disclaimer opinion (WDP) from the BPK, indicating that the financial statements of the Bogor City Government have not yet reached the highest predicate in the form of an unqualified opinion (WTP). This study aims to analyze the quality of the financial statements of the Bogor City Government and formulate strategies to improve the quality of financial statements in the Bogor City Government. The analysis used in the first objective of this study is the descriptive method, while the second objective uses the SWOT analysis method. The study results show that (1) the quality of the local government financial statements (LKPD) of the Bogor City Government is fairly good; (2) clear job descriptions for financial managers are the main strength factor, while the lack of knowledge transfer about financial management is the dominant weakness factor, open selection for occupying position of echelon II is the highest opportunity factor, and the moratorium on the recruitment of human resources for the regional financial management apparatus through the selection of civil servants is the highest challenge factor. Keywords: Finance, Quality, Strategy, Human Resources, SWOT